THE EFFECTIVENESS OF USING SKIMMING AND SCANNING TECHNIQUIE FOR TEACHING READING COMPREHENSION AT JUNIOR HIGH SCHOOL - Misfaatin; Ria Kamilah Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to investigate the effectiveness of skimming and scanning techniques in improving students’ reading comprehension. This research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants consisted of 23 eighth-grade students at junior high school. Data were collected through reading comprehension tests administered before and after the treatment. The pre-test results showed that students’ reading comprehension was relatively low, with a mean score of 46.52. After the implementation of skimming and scanning techniques, the post-test mean score increased significantly to 89.13. The result of the paired sample t-test showed a significance value of 0.001 (p < 0.05), indicating a statistically significant improvement. These findings demonstrate that skimming and scanning techniques are effective in enhancing students’ reading comprehension. Therefore, these techniques are recommended as effective strategies in teaching reading in EFL classrooms.